The impact of the WTO Agreement on TRIPS (trade-related aspects of intellectual property rights) on EC law : a challenge to regionalism - Einhorn, Talia (1998)
Examines the underlying rationale for TRIPs, and its two fundamental principles, the National Treatment principle and the Most-Favoured-Nation principle, and evaluates their impact on EC law.